Torsional fatigue behavior of wrought and additive manufactured Ti-6Al-4V by powder bed fusion including surface finish effect. (June 2017) - Fatemi, Ali; Molaei, Reza; Sharifimehr, Shahriar; Shamsaei, Nima; Phan, Nam
Highlights: Torsion fatigue of powder bed fusion additive manufactured (AM) Ti-6Al-4V. Surface finish and heat treatment effects on torsion fatigue of AM Ti-6Al-4V. Damage mechanism and effect of defects in torsion fatigue of AM Ti-6Al-4V. Torsion fatigue behavior and failure mechanism of wrought Ti-6Al-4V. Abstract: Additive manufacturing (AM) is a state of the art technology enabling fabrication of complex geometries, in addition to providing other advantages as compared to the traditional subtractive manufacturing methods. Powder bed fusion (PBF) is one of the most commonly used metal AM processes that uses laser to melt particles on the bed of metallic powder. Ti-6Al-4V is a common alloy made by this process and has applications in many industries, in particular aerospace and medical industries. Understanding mechanical performance of the additively manufactured materials and components for critical load bearing applications is still in early stages. As such components are typically subjected to cyclic loading, fatigue failure is a major consideration in their design. In addition, due to the multiaxial nature of the loading and/or complex geometries manufactured by AM, the state of stress often includes both normal and shear stresses. However, all the studies so far on fatigue behavior of additive manufactured metals have only considered axial loading, resulting in normal stresses. This study is on torsional fatigue behavior producing shear stresses and, therefore, addresses a major gap in understanding the mechanical behavior of additive manufactured metals in general and for PBF Ti-6Al-4V alloy in particular. In this study, thin-walled tubular specimens made of both wrought and AM Ti-6Al-4V were subjected to monotonic as well as cyclic torsional loads to study and compare their shear deformation and fatigue behaviors. Failure mechanisms in different life regimes and the effects of heat treatment and surface finish were also evaluated.